SYNTHESIS OF 2-OXAZOLINE BISMACROMONOMER AND THEIR POLYMERIZATION - Carlos Rueda, Juan (2017)
In this research was studied the synthesis of bismacromonomer of 2-methyl-2-oxazoline (MeOXA) and 2-(2-metoxycarbonylethyl)-2-oxazoline (EsterOxa) and their polymerization with N-isopropylacrylamide and bisacrylamide for the elaboration of thermosensitive hydrogels. The 2-oxazoline bismacromonomer was structurally characterized by nuclear magnetic resonance (NMR) and was determined that it had a polymerization degree of 8 and the content of EsterOxa was 25% mol. The hydrogels were hydrolysed and the generated carboxylic acid groups were transformed into thiol groups which were later complexed with auric ions. The auric ions were reduced and gold nanoparticles (NP-Au) were obtained in situ in hydrogels. The hydrogels were characterized by the water-absorbing capacity and their sensitivity to temperature. This sensitivity was evidenced by the expansion or contraction of hydrogel volume due to the decrease or incresase of temperature, respectively. The gold nanoparticles (NP-Au) content in the hydrogel were characterized by their tipical superficial plasmon resonance at 525 nm (UV/Vis) and the CEM electron microscopy showed the presence of gold nanoparticles within the hydrogels in a range of sizes from 5 to 250 nm. The NP-Au increased the temperature sensitivity of the hydrogel and the conformational transition occurred at higher temperature.